2016
DOI: 10.1007/s12020-016-0982-x
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy is associated with microcalcification and higher AP/T ratio in ultrasonography, but not with Hashimoto’s thyroiditis in histopathology in patients with thyroid nodules evaluated as Bethesda Category III (AUS/FLUS) in cytology

Abstract: The predictors of malignancy are important for the decision of appropriate management in nodules with atypia of undetermined significance/follicular lesion of undetermined significance (AUS/FLUS). Our aim was to determine the ultrasonographical, clinical, and biochemical predictors of malignancy in these patients. A total of 427 patients with cytologically Bethesda Category III (AUS/FLUS) thyroid nodules were included in this retrospective study. We divided the nodules into two subgroups according to the histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 53 publications
2
23
0
Order By: Relevance
“…Figure shows the procedures of this study, which screened 368 studies. After reading full texts of the studies, 16 publications were included in the meta‐analysis . Table shows the characteristics included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure shows the procedures of this study, which screened 368 studies. After reading full texts of the studies, 16 publications were included in the meta‐analysis . Table shows the characteristics included studies.…”
Section: Resultsmentioning
confidence: 99%
“…After reading full texts of the studies, 16 publications were included in the meta-analysis. 9,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Table 3 shows the characteristics included studies. All studies had sufficient data to calculate the associations between risk factors and nodules.…”
Section: Discussionmentioning
confidence: 99%
“…The use of US in this topic was largely published in the past 9 and controversial data have been reported also in the most recent papers. 16 Instead, in a paper by Batawil et al malignancy was significantly associated with solid nodule structure (RR 2.6) and irregular border (RR 3.6). 16 Instead, in a paper by Batawil et al malignancy was significantly associated with solid nodule structure (RR 2.6) and irregular border (RR 3.6).…”
Section: Discussionmentioning
confidence: 96%
“…The use of US in this topic was largely published in the past 9 and controversial data have been reported also in the most recent papers. [16][17][18][19] Topaloglu et al found that a higher anteroposterior/transverse ratio and microcalcifications were independently associated with malignancy with highest sensitivity and specificity for cutoff value of AP/T ratio 0.81. 16 Instead, in a paper by Batawil et al malignancy was significantly associated with solid nodule structure (RR 2.6) and irregular border (RR 3.6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation